2013
DOI: 10.4236/ajibm.2013.38079
|View full text |Cite
|
Sign up to set email alerts
|

Applying a SERVQUAL Model to Measure the Impact of Service Quality on Customer Loyalty among Local Saudi Banks in Riyadh

Abstract: This paper evaluates the impact of service quality underlying the SERVQUAL model on customer loyalty, with customer satisfaction mediating these variables. This analytical study is mainly based on the primary data collected through a questionnaire that was personally administered to 422 individuals selected from five local banks in Riyadh, Saudi Arabia. The findings indicate that improving service quality can help to enhance customer loyalty. Empathy, assurance, and reliability are the service quality dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 34 publications
2
16
0
1
Order By: Relevance
“…In fact, Nijssen, and Douglas (2004) questioned the validity of applying the findings from developed countries to smaller, less developed countries. It is not always possible to apply the research output from developed countries, such as the United States to less developed countries, such as Saudi Arabia (Abbas, 2013). Therefore, the aims of the present study were to investigate the effect of human resource strategies as a mediator between leadership style and organizational performance in the context of Saudi Arabia.…”
Section: Aim Of the Studymentioning
confidence: 98%
See 1 more Smart Citation
“…In fact, Nijssen, and Douglas (2004) questioned the validity of applying the findings from developed countries to smaller, less developed countries. It is not always possible to apply the research output from developed countries, such as the United States to less developed countries, such as Saudi Arabia (Abbas, 2013). Therefore, the aims of the present study were to investigate the effect of human resource strategies as a mediator between leadership style and organizational performance in the context of Saudi Arabia.…”
Section: Aim Of the Studymentioning
confidence: 98%
“…While different studies have investigated the effect that HR strategy and leadership styles have on an organization's achievement, most such studies have been done in developed countries (Abbas, 2013). In fact, Nijssen, and Douglas (2004) questioned the validity of applying the findings from developed countries to smaller, less developed countries.…”
Section: Aim Of the Studymentioning
confidence: 99%
“…A literature review by Albarq (2013) identified that few studies have applied the SERVQUAL model to customer loyalty in developing countries. If managers in the banking industry can understand the impact that the SQ underlying the SERVQUAL model has on customer loyalty, they may be able to focus their efforts on the areas that make the greatest contribution to customer retention.…”
Section: Tangiblesmentioning
confidence: 99%
“…Saudi banks are facing actually a hostile competition (Albarq, 2014) which motivates those banks to improve the quality of their provided services to meet their customers' expectations which will increase customer loyalty and satisfaction (Albarq, 2013). …”
Section: Previous Researches On Customers' Expectations and Perceptiomentioning
confidence: 99%
“…Also the study indicates that there is a need for quality improvement and that the dimensions of service quality insuring this positive impact are Reliability and Empathy. (Albarq, 2013). …”
Section: Previous Researches On Customers' Expectations and Perceptiomentioning
confidence: 99%